Preparation of Bamboo-Like Carbon Nanotube Loaded Piezoresistive Polyurethane-Silicone Rubber Composite - Mohammed Nabeel; Varga Miklós; Kuzsela László; Filep Ádám; Bela Fiser; Fiser Béla; Фішер Бейло; Viskolcz Béla; Kollar Mariann; Vanyorek László (MDPI, 2021)
Abstract. In this study, a novel technology is reported to prepare a piezoresistive polyurethanesilicone rubber nanocomposite. Polyurethane (PU) foam was loaded with a nitrogen-doped bambooshaped carbon nanotube (N-BCNT) by using dip-coating, and then, impregnated with silicone rubber. PU was used as a supporting substrate for N-BCNT, while silicone rubber was applied to fill the pores of the foam to improve recoverability, compressive strength, and durability. The composite displays good electrical conductivity, short response time, and excellent repeatability. The resistance was reduced when the amount of N-BCNT (0.43 wt %) was increased due to the expanded conductive path for electron transport. The piezoresistive composite has been successfully tested in many applications, such as human monitoring and finger touch detection.
Editorial Board: https://www.mdpi.com/journal/polymers/editors
Contents: https://www.mdpi.com/2073-4360/13/13
Keywords: nitrogen-doped bamboo-shaped carbon nanotube; N-BCNT; PU; nanofiller; piezoresistive